Kritik Informasi di Era Digital : Pengabdian Masyarakat dalam Edukasi Anti-Hoaks bagi Pemuda Gampong Lamblang Manyang - Depita Kardiati; Abdul Hafiz; Rauzi Ramazalena; Syarifah Chairunnisak; Reza Fahlevi; Muslem Muslem (BADAN PENERBIT STIEPARI PRESS, 2025)
: The rapid development of information technology in the digital era has brought new challenges, particularly the widespread circulation of hoaxes among the public—especially among the younger generation who are active on social media but often lack adequate digital literacy skills. This community service initiative aims to strengthen the critical capacity of the youth in Gampong Lamblang Manyang through a participatory, educational approach. The method used is Participatory Action Research (PAR), involving youth in the planning, implementation, and evaluation stages of the program. The results show an increased understanding among participants regarding the characteristics of hoaxes and how to verify information. Behavioral changes were also observed in participants’ more thoughtful and responsible use of social media. They also demonstrated greater participation in critical discussions within the village and took the initiative to continue educational efforts independently through youth groups. This activity successfully fostered critical awareness, strengthened the role of youth as agents of information literacy, and encouraged collective concern for the importance of information filtering in the digital age.